HISTOPATHOLOGICAL RESPONSES IN LIVER, KIDNEY, INTESTINE AND TESTIS OF ALBINO MICE AFTER EXPOSURE TO ALUMINIUM - N. JOHN SUSHMA; B. MAHITHA; P. L.SRAVANTHI; S. PRIYANKA; K. JAYANTHA RAO (International Journal of Pharma and Bio Sciences, 2011)
We have examined the effect of aluminum (Al) acetate on albino mice. Different doses of aluminum acetate (3.5 mg/kg body weight (b.w), intraperitoneal injection., single dose:3.5mg/kg b.w, double dose:3.5 mg/kg b.w, with 72 h interval on 1st and 4th day and multiple doses: 3.5 mg/kg b.w, with 72 h interval on 1st , 4th ,7th and 10th day) resulted alterations in tissue histology of liver, kidney, intestine and testis. Our findings indicate that the pronounced pathological changes in multiple doses compared to double and single dose administered mice. We found that dose dependent exposure of aluminum acetate causes deleterious effects and make them less fit for better survival.